Strategies for Interorganizational Relationships in the Implementation of the “Merdeka Belajar Kampus Merdeka” Initiative at Private Universities in Gorontalo - Rizal Rizal; Ansar Ansar; Sastro Mustapa Wantu; Yanti Aneta (West Science Interdisciplinary Studies, 2026)
This study aims to analyze the Interorganizational Relationship (IOR) strategy in the implementation of the Independent Learning (Merdeka Belajar Kampus Merdeka MBKM) policy at private universities (PTS) in Gorontalo Province, emphasizing the dimensions of coordination, cooperation, and collaboration between organizations. In the context of MBKM, interorganizational relationships are key to expanding resource access, strengthening curriculum relevance, and improving the quality of experiential learning. This study uses a qualitative approach with a case study method in several private universities that have implemented the MBKM program in Gorontalo. Informants were purposively selected from the leadership of private universities, LLDIKTI Region XVI, and APTISI Gorontalo Region, with data collection techniques through in-depth interviews, participatory observation, and documentation studies. The results show that coordination between private universities is facilitated by APTISI and LLDIKTI through meeting forums that regularly discuss MBKM implementation, so that communication flows and information exchange are relatively well established. However, substantive cooperation and collaboration between private universities in the form of student exchanges and lecturer teaching outside their home base have hardly materialized, although these two indicators have great potential for development based on the MBKM Key Performance Indicators. Field findings reveal that weak cooperation and collaboration are influenced by institutional egos, competitive tendencies in student recruitment, similar capacities and resources across private universities, and complex internal bureaucracy. This study confirms that the success of MBKM implementation in Gorontalo's private universities is largely determined by the institution's ability to build inter-organizational networks that are not only coordinative but also collaborative and mutually beneficial in a sustainable manner.